2020
DOI: 10.1002/ccd.29097
|View full text |Cite
|
Sign up to set email alerts
|

Stenting techniques for coronary bifurcation lesions: Evidence from a network meta‐analysis of randomized clinical trials

Abstract: Objectives We conducted a systematic review and network meta‐analysis of available randomized clinical trials (RCTs) to compare cardiovascular outcomes involving stenting techniques in coronary bifurcation lesions. Background Although provisional stenting of the main branch and balloon angioplasty of the side branch is considered the standard approach, the use of two stents is often pursued with a wide variety of bifurcation stenting techniques available. Methods We searched PubMed, Embase, the Cochrane Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…Among the different 2-stent techniques (summarized in the MADS classification and its amendments [4]), the double-kissing and crush (DK-crush) has been shown to result in improved stent expansion at the side branch (SB) ostium, and in reduced neointimal proliferation during 8-month follow-up [5]. DK-crush was associated with lower rates of target-lesion revascularization as compared with provisional or culotte stenting in both non-left main and left main coronary bifurcation lesions [6][7][8][9]. As compared to older techniques, DK-crush requires an additional kissing balloon dilation prior to main branch (MB) stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different 2-stent techniques (summarized in the MADS classification and its amendments [4]), the double-kissing and crush (DK-crush) has been shown to result in improved stent expansion at the side branch (SB) ostium, and in reduced neointimal proliferation during 8-month follow-up [5]. DK-crush was associated with lower rates of target-lesion revascularization as compared with provisional or culotte stenting in both non-left main and left main coronary bifurcation lesions [6][7][8][9]. As compared to older techniques, DK-crush requires an additional kissing balloon dilation prior to main branch (MB) stenting.…”
Section: Introductionmentioning
confidence: 99%
“…In complex CBL, a two-stent bifurcation technique provides better results than provisional stenting, 12 while a single-stent approach should remain the preferred technique in the setting of simple bifurcations. 13 , 14 However, it is still controversial which technique should be preferred during single-stenting. The POT-side-POT sequence respects fractal geometry by reducing SB ostium stent-strut obstruction, providing perfect proximal stent apposition with almost perfect circularity, reducing ellipticity index, proximal area overstretch, and global strut malapposition.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses consistently demonstrated that DK crush was associated with fewer coronary events and complications than bifurcation techniques. [22][23][24][25] In a recent network meta-analysis, Di Gioia et al [23] analyzed 21 randomized studies of 5711 patients, which showed that the DK-crush stenting technique was associated with less occurrence of MACE than those treated using PS mainly driven by a reduction in TLR. More specifically, no significant differences among techniques were observed in cardiac death, MI, and stent thrombosis.…”
Section: Meta-analysismentioning
confidence: 99%
“…In recent times, an abundance of scientific and clinical evidence has been obtained to demonstrate the effectiveness and safety of this specific 2-stent technique. [14–27]…”
Section: Introductionmentioning
confidence: 99%